A Refined Service-Seeking Web Application: Web Application with Categorized Listings, Event Planning and Service Requesting (Business Side) - Kontou, Konstantinos (My University, 2024)
This thesis examines how to develop a service-seeking web application to bridge the gap between businesses offering services and users needing them. It provides an organized platform with classified listings, making it easy for customers to locate and evaluate various business services. There are also eventplanning tools that can assist users in managing and organizing events using providers’ know-how. These tools are available and beneficial to anybody, regardless of background or knowledge level. In addition, the service request feature enables users to submit and monitor their requests, thereby ensuring seamless communication between users and businesses. After getting user feedback throughout its development process, we modified this web application to align it more closely with real-life challenges encountered in seeking services and managing events. This thesis discusses a web application’s design, implementation, and future potentials, which shows how it enhances user satisfaction and operational efficiency on both sides – for users and companies providing services.
Keywords: Web Application Design; organized platform